Vanishing: A Novel - Lyons, Jeanette (2015)
My thesis is a novel titled Vanishing. It is a work of speculative fiction set in Western Australia. The setting is contemporary, although in a departure from history, the state of Western Australia has seceded from Australia and exists as an independent nation. The government has evolved into a liberal model of tolerance and invited the maligned races of folklore to immigrate. To the world’s astonishment, the Snitches emerge from the wilderness and settle in their new homeland. Their unique mind-reading powers are pressed into service as the government strives to eradicate offensive speech and offensive thought. The novel’s protagonist is Hunter Jones, an average guy with an irreverent attitude towards the government’s social engineering agenda. His ordinary life is rocked when twin brother Sean is abducted after a night out with their parents. Hunter’s search for his missing brother is stymied by the loss of anything to do with Sean—personal effects go missing and memories are erased. The unbreakable bond shared by twins means that Hunter is the only person who remembers Sean ever existed.